A Rare Case of Gallbladder Tuberculosis Masquerading as Chronic Calculous Cholecystitis - Pavithra, Hardanahalli Nagaraju; Nayyar, Ankush; Kallianpur, Ashwin Anand; Garg, Puneet Kumar; Uttam, Neha Gopal (Journal of Gastrointestinal Infections, 2024)
Gallbladder being an uncommon site of tuberculosis, we are presenting a case of tubercular cholecystitis in a 61-year-old female who presented with pain abdomen and was operated for cholelithiasis. The diagnosis was clinched on histopathological examination. She was treated accordingly and has responded well for antitubercular therapy.This case is unique as the patient had no symptoms of gastrointestinal or pulmonary tuberculosis. It was only after histopathological examination, the diagnosis was reached.
Keywords: extrapulmonary tuberculosis; gallbladder tuberculosis; miliary tuberculosis